Toxicity Test, Antibacterial and Antioxidant Activity of Simargaolgaol Plant Stem Extract (Aglaonema modestum Schott ex Engl) - Salsabila, Fuaddinda Putri; Riris, Ida Duma; Sihombing, Junifa Layla; H, Herlinawati; Roza, Destria (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The simargaolgaol plant (Aglaonema modestum Schott ex Engl) is one of the plants that grow wild in the Barus forest area of Central Tapanuli, North Sumatra which is used by local people as a traditional medicinal plant. This study aims to determine the toxicity properties by BSLT method, antibacterial activity by disc diffusion method and antioxidant activity by DPPH method. Toxicity test results of simargaolgaol stem extract (Aglaonema modestum Schott ex Engl) against Artemia salina Leach larvae showed that n-hexane extract has toxic properties with an LC50 value of 24.424 ppm (toxic category), ethyl acetate extract with an LC50 value of 40,693 ppm (toxic category) and ethanol extract with an LC50 value of 25,830 ppm (toxic category). The results of antibacterial activity showed that ethyl acetate extract (semipolar) with a concentration of 10% had the greatest antibacterial potential against Escherichia coli bacteria with an inhibition zone of about 14.3 mm (strong category). The results of antioxidant activity of ethanol extract of simargaolgaol stems have an IC50 value of 28.075 ppm and Vitamin C has an IC50 value of 36.867 ppm. Thus, based on the results of the IC50 value, it can be seen that the ethanol extract of simargaolgaol stems has strong antioxidant activity compared to Vitamin C as a comparison.